Comparative Study of the Influence of Heat Treatment and Additive Manufacturing Process (LMD & L-PBF) on the Mechanical Properties of Specimens Manufactured from 1.2709 - Gnaase, Stefan; Niggemeyer, Dennis; Lehnert, Dennis; Bödger, Christian; Tröster, Thomas (Crystals)
(1) This work answers the question of whether and to what extent there is a significant difference in mechanical properties when different additive manufacturing processes are applied to the material 1.2709. The Laser-Powder-Bed-Fusion (L-PBF) and Laser-Metal-Deposition (LMD) processes are considered, as they differ fundamentally in the way a part is manufactured. (2) Known process parameters for low-porosity parts were used to fabricate tensile strength specimens. Half of the specimens were heat-treated, and all specimens were tested for mechanical properties in a quasi-static tensile test. In addition, the material hardness was determined. (3) It was found that, firstly, heat treatment resulted in a sharp increase in mechanical properties such as hardness, elastic modulus, yield strength and ultimate strength. In addition to the increase in these properties, the elongation at break also decreases significantly after heat treatment. The choice of process, on the other hand, does not give either process a clear advantage in terms of mechanical properties but shows that it is necessary to consider the essential mechanical properties for a desired application.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Investigation of the influence of process parameters on productivity in the LPBF process for the material Inconel 718 - Bödger, Christian; Gnaase, Stefan; Lehnert, Dennis; Tröster, Thomas (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The nickel-based alloy Inconel 718, which is used in aerospace technology, poses a great challenge to conventional machining due to its high strain hardening and toughness. Here, the laser powder bed fusion process (LPBF) offers an alternative with potential savings if sufficiently high productivity can be achieved. Based on the parameter study carried out, starting from the SLM Solutions standard parameters for the manufacturing of components, exposure parameters could be developed to realize manufacturing with 120 μm and 150 μm layer thickness, with almost the same geometric accuracy. For this purpose, the process parameters of laser power, focus diameter, hatch distance and scan speed were varied. The negative defocusing of the laser showed a positive effect on the density of the parts, realizing densities ≥ 99.94 %, with high dimensional stability and good mechanical properties. Considering the reduced manufacturing time of up to 61 %, a significant increase in productivity was achieved.

Processing Short Fiber-reinforced Polymers in the Fused Deposition Modeling Process - Schumacher, Christian; Schöppner, Volker; Gnaase, Stefan (Proceedings of the 29th Annual InternationalSolid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
By adding fibers to a polymer matrix, a reinforcement of the material can be achieved. Shortfiber-reinforced polymers can easily be processed by the Fused Deposition Modeling (FDM)process without major modifications to the processing machine. For instance, short fiber-reinforcedfilaments can be processed to produce short fiber-reinforced components in the FDM process. Inmany other additive manufacturing processes this is not possible at this low cost. The choice of thematrix material, fiber type, fiber length and fiber orientation have a major influence on theproperties of the produced component. In this paper, short fiber-reinforced filaments are processedby the FDM process. The processing properties and the resulting part properties are investigatedwith regard to fiber-specific influences. Additionally, the effects of different strand geometries andthus changed flow fields on the fiber orientation and mechanical part properties are investigated.